Intratumoral microbiota, fatty acid metabolism, and tumor microenvironment constitute an unresolved trinity in colon adenocarcinoma - Guangyi Liu; Kun Liu; Lei Ji; Yang Li (Scientific Reports)
Abstract The intratumoral microbiota, fatty acid metabolism (FAM), and tumor microenvironment (TME) all provide insights into the management of colon adenocarcinoma (COAD). But the biological link among the three remains unclear. Here, we analyzed intratumoral microbiome samples and matched host transcriptome samples from 420 patients with COAD in The Cancer Genome Atlas (TCGA). All patients were divided into two subtypes (FAM_high and FAM_low) based on the Gene set variation analysis (GSVA) score of FAM pathway. Furthermore, we found significant difference in the intratumoral microbiota signatures between the two subtypes. In-depth analysis suggested that specific microbes in tumors may indirectly modify the TME, particularly stromal cell populations, by modulating the FAM process. More importantly, the crosstalk between the three can have a significant impact on prognosis, response to immunotherapy, and drug sensitivity of patients. Pathological image profiling showed that changes in the TME originating from intratumoral microbiota disturbance could be reflected in pathological image features. In summary, our study provides novel insights into the biological links among the intratumoral microbiota, FAM, and the TME in COAD, and offer guidance for the therapeutic opportunities that target intratumoral microbes.